2019
DOI: 10.3390/v11111075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Characterization of the First Cowpox Virus Isolate Derived from a Bank Vole

Abstract: Cowpox virus (CPXV) is a zoonotic orthopoxvirus (OPV) that infects a wide range of mammals. CPXV-specific DNA and antibodies were detected in different vole species, such as common voles (Microtus arvalis) and bank voles (Myodes glareolus). Therefore, voles are the putative main reservoir host of CPXV. However, CPXV was up to now only isolated from common voles. Here we report the detection and isolation of a bank vole-derived CPXV strain (GerMygEK 938/17) resulting from a large-scale screening of bank voles c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 57 publications
3
19
1
1
Order By: Relevance
“…Along with a previous study, we concluded that in vitro assays could not predict in vivo properties or virulence differences [39]. The same was observed in a recent study for the new CPXV strain GerMygEK 938/17 in comparison to Brighton Red and CPXV FM2292 on different cell lines (bank vole-and common vole-derived kidney cells and Vero76 cells) [32].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Along with a previous study, we concluded that in vitro assays could not predict in vivo properties or virulence differences [39]. The same was observed in a recent study for the new CPXV strain GerMygEK 938/17 in comparison to Brighton Red and CPXV FM2292 on different cell lines (bank vole-and common vole-derived kidney cells and Vero76 cells) [32].…”
Section: Discussionsupporting
confidence: 80%
“…In 2018, we successfully isolated the first bank vole-derived CPXV strain, GerMygEK 938/17 [32]. This new isolate provided the possibility to test the susceptibility of bank voles by experimental infection with a bank vole-derived strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations